Z dějin kontaktů dvou blízkých slovanských jazyků, češtiny a slovenštiny - Musilová, Květoslava; Dobrotová, Ivana (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2012)
Kulturní a jazykové vztahy mezi Čechy a Slováky existovaly ještě před vznikem společného státu. V rámci Československa (od r. 1918) se začaly vyvíjet na kvalitativně jiné úrovni: teorie čechoslovakismu (tj. jednoho československého národa a jednoho československého jazyka ve dvou zněních – českém a slovenském) prostřednictvím jazykového zákona (1920) napomáhala konvergenci obou jazyků. Teprve Ústava 9. května deklarovala rovnoprávnost obou národů a zrušila jazykový zákon z r. 1920. Pro komunikaci Čechů a Slováků je typická dvojjazykovost, která je umožněna extrémní genetickou blízkostí obou jazyků. Ani rozdělení státu (1992), kdy byly přímé i nepřímé kontakty zredukovány a nastala tak očekávaná divergence češtiny a slovenštiny, nevznikla mezi oběma jazyky výrazná komunikační bariéra. Tuto skutečnost dokazují také sociolingvistické výzkumy zaměřené na některé aspekty česko-slovenských (nejen) jazykových vztahů.

Cultural and linguistic relations between Czechs and Slovaks had already existed before establishment of joined State. In Czechoslovakia (since 1918), these relations started to evolve on a qualitatively different basis: theory of czechoslovakism (i.e. one Czechoslovak nation and one Czechoslovak language in two versions – Czech and Slovak) through the 1920 Language Act helped to converge both languages. It was only the Constitution from May 9 that declared equal rights for both of nations and terminated 1920 Language Act. The communication of Czechs and Slovaks is characterised by „di-lingualism”, which is possible due to an extreme genetic vicinity of both languages. Even after the State secession (1993), accompanied by the reduction of direct and indirect contacts resulting in expected divergence of Czech and Slovak languages, a substantial barrier in communication between the two languages has not occurred. This fact is also proved by socio-linguistic researches focusing on some aspects of Czech-Slovak (not only) linguistic relations.
Two close slavic languages, Czech and Slovak – on history of contacts
Keywords: Lingvistika; Linguistic; Sociolingvistika; Sociolinguistic; Jazykové kontakty; Language contacts; Čeština; Czech language; Slovenština; Slovak language